Management of Mucocele of the Glands of BlandinNuhn With a High-Intensity Laser: A Case Report: Mucocele Treated With High-Intensity Laser - Kato, Rayla Bentes; Jácome-Santos, Humberto; Couto, Ana Paula Guerreiro Rodrigues; Abreu, Lucas Guimarães; Mesquita, Ricardo Alves; Kato, Camila Nazaré Alves de Oliveira (Journal of Lasers in Medical Sciences, 2021)
Introduction: The glands of Blandin–Nuhn are mucous and serous salivary glands situated on both sides of the midline of the ventral surface of the tongue. In this area, a mucocele generally results from trauma. The diagnosis of mucoceles is based on clinical and histopathological examinations and the recommended treatment is surgical excision. Case report: This report describes a case of mucocele of the glands of Blandin-Nuhn (MGBN) affecting a 20-year-old male. Oval-shaped swelling with a smooth and bright surface of soft consistency was observed on the ventral surface of the individual’s tongue. The diagnostic hypothesis was mucocele. Surgical excision was performed in a single session with a diode laser. A histopathological examination revealed mucus extravasating into connective tissue, with foamy macrophages and granulation tissue. Conclusion: The high-intensity laser was a safe and effective tool for treating MGBN. No need for a suture, minimal or no intraoperative bleeding, and a minimal report of pain and edema by the patient were observed. A diode laser may be a helpful tool because it is less invasive and it is safe and effective. DOI:10.34172/jlms.2021.27